Application of o-Carboxyphenylazo-bis-acetoxime in Spectrophotometric Determination of Iron(III) - Khan, Saba; Khanam, Rehana (Asian Journal of Chemistry, 2010)
o-Carboxyphenylazo-bis-acetoxime has been used for spectrophotometric determination of iron(III) at 376 nm, keeping the pH at 2.8-4.0. Beer's law is obeyed in the range (4 to 24) × 10-5 M. The molar absorptivity and Sandell's sensitivity values are 2.446 dm3 mol-1 cm-1 and 22.83 ng cm-2, respectively.